UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA MELALUI MODEL NUMBERED HEAD TOGETHER (NHT) PADA SISWA KELAS VIII SMP PGRI 3 BANDAR LAMPUNG - Nurdiana, Aty; Haryanto, Haryanto (Epsilon: Jurnal Pendidikan Matematika, 2019)
This study relates to the lack of optimal activity and learning outcomes of class VIII students of SMP PGRI 3 Bandar Lampung. The aim is to improve the activities and results of learning mathematics through the Numbered Head Together (NHT) learning model. The research conducted was classroom action research through 3 cycles using the NHT learning model. Based on the results of the study, there was an increase in the activities and learning outcomes of students from before the implementation of the study until after the research was conducted. The average activity of students at the time before the study was 52.31% and the percentage of completeness was 8.33%. In the first cycle the average student activity increased to 60.77% with a percentage of completeness of 66.67%. The average activity of students in cycle II increased again to 68.08% with the percentage of completeness reaching 75.00%. In the third cycle the average activity of students became 79.62% and the percentage of completeness was 83.33%. Based on these results, it can be concluded that the NHT learning model is more effectively used in an effort to improve the activity and learning outcomes of class VIII students of SMP PGRI 3 Bandar Lampung.